Peningkatan Kadar Metana Biogas dengan Metode Adsorpsi Menggunakan Adsorben Karbon Aktif Tempurung Kelapa dan Zeolit Alam pada Berbagai Laju Alir (Studi Kasus: Desa Carangwulung) - Muhammad Fathin Taqiyuddin; Firra Rosariawari; Praditya Sigit Ardisty Sitogasa (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Biogas is a potential renewable energy source, but the content of impurity gases such as carbon dioxide (CO2) and hydrogen sulfide (H2S) reduces its quality and efficiency as a fuel. This study aims to analyze the effectiveness of the adsorption method using a combination of coconut shell activated carbon and natural zeolite in increasing methane (CH4) levels in biogas. The biogas used was produced from a cattle farm in Carangwulung Village. The variables tested included variations in the composition of activated carbon (C) and zeolite (Z) adsorbents with biogas flow rates (0.2; 0.4; and 0.6 L/min). The test was carried out with an adsorbent mass of 300 grams activated by KOH and the resulting pressure ranged from 9–13 mbar. The results showed that the adsorbent composition of 50C:50Z with a flow rate of 0.2 L/min gave the best performance. Under these conditions, CH4 levels could increase from 45% to 87%, where there was an increase in methane by 48%. The adsorption process at low flow rates provides optimal contact time between gas and adsorbent, thus increasing the efficiency of increasing CH4 levels. Thus, the combination of coconut shell activated carbon and natural zeolite at low flow rates is effective in improving biogas quality through the adsorption process.